Production of Sonali chicken in selected areas of Gazipur district - an economic study - Uddin, MT; Mitu, SJ; Begum, IA (Bangladesh Journal of Animal Science, 2014)
This study attempts to conduct an economic analysis and resource use efficiency for Sonali chicken production covering five villages of Sadar Upazila under Gazipur district. Primary data were collected from 60 purposively selected Sonali chicken rearers for this study. Descriptive and functional analysis were employed to achieve the objectives of the study. The major findings of the study are that total cost for 1000 birds were estimated at Tk. 120613 per batch. Average gross margin and average net returns for 1000 birds was calculated at Tk. 57240 and Tk. 52059 per batch. An average gross return for 1000 birds was estimated at Tk. 172672 per batch. Benefit cost ratio was found 1.4 for Sonali chicken production. Labour, veterinary and medicine and electricity cost had positive and significant impact on Sonali chicken production. Resource use efficiency was calculated by the ratio of marginal value product and marginal factor cost. Finally, the study also identified some of the major problems associated with Sonali chicken farming and suggested some possible steps for overcoming these problems. DOI: http://dx.doi.org/10.3329/bjas.v43i1.19386 Bang. J. Anim. Sci. 2014. 43 (1): 56-61